2022
DOI: 10.1038/s41598-022-06888-z
|View full text |Cite
|
Sign up to set email alerts
|

Heat inactivation of clinical COVID-19 samples on an industrial scale for low risk and efficient high-throughput qRT-PCR diagnostic testing

Abstract: We report the development of a large scale process for heat inactivation of clinical COVID-19 samples prior to laboratory processing for detection of SARS-CoV-2 by RT-qPCR. With more than 266 million confirmed cases, over 5.26 million deaths already recorded at the time of writing, COVID-19 continues to spread in many parts of the world. Consequently, mass testing for SARS-CoV-2 will remain at the forefront of the COVID-19 response and prevention for the near future. Due to biosafety considerations the standar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Despite the loss in analytical sensitivity, the overall agreement was 99.3% combined without C q stratification of results. We note that other studies have focused on positive sample comparisons and the number of negative samples tested with extraction-free approaches has been limited or absent ( 8 , 9 , 11 , 18 ). Diagnostic PCR assays are optimized for purified nucleic acids in terms of primer-probe stringency and test performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the loss in analytical sensitivity, the overall agreement was 99.3% combined without C q stratification of results. We note that other studies have focused on positive sample comparisons and the number of negative samples tested with extraction-free approaches has been limited or absent ( 8 , 9 , 11 , 18 ). Diagnostic PCR assays are optimized for purified nucleic acids in terms of primer-probe stringency and test performance.…”
Section: Discussionmentioning
confidence: 99%
“…Optimization experiments have shown that high temperature and short durations (95 to 98°C for 5 to 15 min) improve (reduce) C q values compared to lower temperature and longer durations (60°C for 30 min) ( 9 ). Heat inactivation prior to testing with extraction-based methods also reduces the sensitivity of SARS-CoV-2 RNA detection ( 4 , 18 , 19 ). Other investigators have shown the addition of proteinase K (55°C for 15 min) followed by heat treatment also improves C q values up to three cycles compared to heat treatment alone ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…As different forms of specimens, including sputum, plasma, and stool can be handled, the methods to inactivate these different samples can vary greatly, but the most common are heat and detergents 11,14,16 . Numerous studies have even described SARS‐CoV‐2 inactivation efficacy with less traditional protocols including ophthalmic solutions or repurposed therapeutic agents 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27]. The methods to inactivate these different samples can vary greatly, but the most common are heat and detergents [20,21,[28][29][30][31]. Numerous studies have even described SARS-CoV-2 inactivation efficacy with less traditional protocols including ophthalmic solutions, repurposed therapeutic agents or ultraviolet C irradiation [28,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…With the unprecedented high demand of diagnostics tests performed around the world, the question of handling and processing such infectious samples remains relevant. Inactivation protocols against viruses have been regularly evaluated in the past, including with heat against influenza [29,30] and SARS-CoV 2003 [31] viruses, as well as with detergents against enveloped herpes simplex and human immunodeficiency virus [32]. Indeed, with over 426 million global COVID-19 cases diagnosed by mid-February 2022 [9], public health laboratories have commissioned incremental changes to logistics processing and staff organization.…”
Section: Introductionmentioning
confidence: 99%